Shirking, Commuting and Labor Market Outcomes - Stephen L. Ross; Yves Zenou (The Research Institute of Industrial Economics (IUI), 2004)
Recent theoretical work has examined the spatial distribution of unemployment using the efficiency wage model as the mechanism by which unemployment arises in the urban economy. This paper extends the standard efficiency wage model in order to allow for behavioral substitution between leisure time at home and effort at work. In equilibrium, residing at a location with a long commute affects the time available for leisure at home and therefore affects the trade-off between effort at work and risk of unemployment. This model implies an empirical relationship between expected commutes and labor market outcomes, which is tested using the metropolitan sample of the American Housing Survey. The empirical results suggest that shirking and leisure are complementary with the marginal benefit of shirking increasing with an individual's net time endowment.
Keywords: J41; R14; 330; Efficiency Wage; Leisure; Urban Unemployment; American Housing Survey; Effizienzlohn; Freizeit; Arbeitsmarkt; USA; Pendelverkehr